Active owners and the failure of newly adopted works councils - Uwe Jirjahn; Jens Mohrenweiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Using representative data from the IAB Establishment Panel, we show that employees in establishments with active owners are less likely to introduce a works council. Moreover, we show that, in case of an introduction, the new works council is less likely to survive if active owners are present. Our findings conform to the hypothesis that active owners oppose codetermination because it reduces the utility they gain from being the ultimate bosses within the establishment.
urn:nbn:de:bsz:180-madoc-349042
Keywords: J50; J53; J54; M54; 330; Active Owner; Works Council Introduction; Works Council Dissolution; Liability of Newness; Employer Resistance to Change